Apoptosis and cell cycle arrest of MCF-7R breast carcinoma cells by bis(phosphane)copper(I) thiocarbamides derivative compounds - Ooi, Kah Kooi (2017)
Previous studies on coordinated gold compounds namely phosphanegold(I) thiocarbamides exhibited promising anti-cancer activities through induction of apoptosis. To a greater extent, current research was advanced to study copper(I) derivatives, namely bis(phosphane)copper(I) thiocarbamides, (Ph3P)2Cu[S=C(OR)N(H)Ph]Cl, with R referring as three different substituent group: methyl (Compound1), ethyl (Compound2), and isopropyl (Compound3); on breast cancer. Among the aggressive cancers reported, breast cancer exhibited poor response to chemotherapy owing to its high cellular glutathione (GSH) levels, high mitochondrial thioredoxin reductase (TrxR) activities and over-activation of NF-κB; hence, contributed for reduced drug’s efficacy and resistance to death-signals. Thus, regulation on GSH, TrxR and NF-κB are suitable targets in current study. The tested copper(I) compounds demonstrated in-vitrocytotoxicity against MCF-7R breast carcinoma cells with micromolar potency. Meanwhile, cytotoxicity testing on normal cells (kidney, breast and heart) suggest Compound1–3are less potent towards normal cells and selective towards breast cancer cells. Inhibition of TrxR yield increase of cellular level of reactive oxygen species and further mitochondria membrane polarization, indicating Compound 1–3 inhibit mitochondrial functionvia oxidative stress. The detailed mechanistic studies demonstratedCompound 1–3 inducedboth intrinsic and extrinsic pathway of apoptosis through upregulation of p53/p73 genes and interaction with cell-death receptor. Also, Compound 1–3arrest the cell cycle of MCF-7R cells through activation of S-phase cell cycle checkpoint via modulation of cyclins and cyclin-dependent kinases. The NF-κB pathway is also down-regulated by Compound 1–3through the regulation of Lys48-and Lys63-linked polyubiquitination. From the summary of apoptosis and cell cycle pathway, it can be concluded different mechanisms are mediated by differing the nature of substituent groups in compounds hence they possess potential as anti-cancer agents.